If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 3) + 3 = 3(2x + 6) + -10 Reorder the terms: 5(3 + 2x) + 3 = 3(2x + 6) + -10 (3 * 5 + 2x * 5) + 3 = 3(2x + 6) + -10 (15 + 10x) + 3 = 3(2x + 6) + -10 Reorder the terms: 15 + 3 + 10x = 3(2x + 6) + -10 Combine like terms: 15 + 3 = 18 18 + 10x = 3(2x + 6) + -10 Reorder the terms: 18 + 10x = 3(6 + 2x) + -10 18 + 10x = (6 * 3 + 2x * 3) + -10 18 + 10x = (18 + 6x) + -10 Reorder the terms: 18 + 10x = 18 + -10 + 6x Combine like terms: 18 + -10 = 8 18 + 10x = 8 + 6x Solving 18 + 10x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 18 + 10x + -6x = 8 + 6x + -6x Combine like terms: 10x + -6x = 4x 18 + 4x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 18 + 4x = 8 + 0 18 + 4x = 8 Add '-18' to each side of the equation. 18 + -18 + 4x = 8 + -18 Combine like terms: 18 + -18 = 0 0 + 4x = 8 + -18 4x = 8 + -18 Combine like terms: 8 + -18 = -10 4x = -10 Divide each side by '4'. x = -2.5 Simplifying x = -2.5
| 60x+11y=1 | | x/27=26 | | X+2=y*5000 | | d=25(20) | | 27/x=26 | | -10-9h-10=-6h+100 | | 0.25p-4.6=3 | | 18+22=-5(7x-8) | | 3X-6whenX=4 | | x+10x-70=2x+3 | | 2(5x-3)-3=6(2x-3)-10 | | 4+5x+x=-56 | | 4x^2=-11 | | 9x-5-5x=3+4x-2 | | -27-3y=-8(6y-5) | | 5x-3=13-83 | | 3xa=3/5 | | 10x-12=8x+42 | | 2a=5b+1 | | 61=7(-1+2v)+2 | | 2x^2-8x=152 | | d=20(35) | | -33+4n=4(n+4)+7n | | 1/3m=14 | | 2.43=log(x) | | -33+4n=4(n+7)+7n | | 3m+100=10 | | -1=2(3x-4)+x | | 2(8x-5)=2x-(-18) | | d=35(10) | | 2b^2-18b+116=0 | | -5g=15 |